Pemanfaatan ChatGPT AI pada Proses Pembelajaran Siswa di SMA X Kota Y - Agus Wagito (SMART : Jurnal Teknologi Informasi dan Komputer, 2025)
The rapid advancement of artificial intelligence (AI) technology, particularly ChatGPT developed by OpenAI, has opened new opportunities in the education sector. However, studies specifically examining how senior high school students in Indonesia use ChatGPT in their learning processes remain limited. This study aims to: (1) analyze patterns of ChatGPT use among students of SMA X, City Y; (2) evaluate the impact of ChatGPT use on learning outcomes from the student perspective; (3) identify the dimensions of use (Accessibility, Usefulness, Ease of Use, Academic Integrity, and Learning Motivation) that receive the highest and lowest assessments; and (4) formulate targeted recommendations for the integration of ChatGPT in high school learning. The research employed a descriptive quantitative approach with a cross-sectional design. Respondents consisted of 120 students actively enrolled in SMA X selected through proportional stratified random sampling. Data were collected via a structured questionnaire covering five dimensions. The User Satisfaction Index (USI) showed an overall score of 74.2% (Good category). The Usefulness dimension obtained the highest score (77.5%), while Academic Integrity received the lowest (64.8%). Gap analysis revealed the largest negative gap in Academic Integrity (gap score: −0.89), indicating this dimension as the most critical area requiring intervention. The novelty of this study lies in its application of five-dimensional gap analysis specifically adapted for AI-based technology use in the secondary school educational context, providing a more actionable diagnostic framework compared to single-score satisfaction surveys previously used in similar studies.